Energy Justice in Electromobility Development: EU and ASEAN Law in a Comparative Context - Nur, Asrul Ibrahim (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
To counteract climate change, various states have adopted innovative laws and solutions. Electromobility as a climate policy is one of the solutions that can contribute to reducing carbon emissions. Furthermore, international organisations such as the European Union (EU) have encouraged member states to develop an electric mobility ecosystem. Moreover, as one of the EU partner organisations, the Association of Southeast Asian Nations (ASEAN) has encouraged member states to adopt similar laws and policies in electromobility innovations. This study examined the EU and ASEAN legal innovations that developed electromobility ecosystems in the context of energy justice comparisons. This paper argues that adopting the principle of energy justice in EU and ASEAN law is highly dependent on the function and role of international organisations in lawmaking. As a climate policy innovation, electromobility is closely related to energy justice for the public. Therefore, analysing the functions and roles of international organisations such as the EU and ASEAN is crucial. The study examined the legal framework adopted by the EU and ASEAN to create an electromobility ecosystem. The purpose of the study was to obtain a comprehensive understanding of the role and function of lawmaking in international organisations supporting climate policy and contributing to the achievement of energy justice.
Keywords: ASEAN, Comparative, Energy Justice, Electromobility, EU.